Testicular function and bone in young men with severe childhood-onset obesity. - Anand-Ivell, Ravinder; Ivell, Richard; Laakso, Saila; Viljakainen, Heli; Lipsanen-Nyman, Marita; Turpeinen, Ursula; Ivaska, Kaisa K; Mäkitie, Outi (Karger, 2018)
Background: Previous studies suggest increased risk for hypoandrogenism and fractures in men with obesity. We aimed to describe the effects of severe childhood-onset obesity on the cross talk between metabolic state, testes and skeleton at late puberty. Methods: A cohort of adolescent and young adult males with severe childhood-onset obesity (n=21, mean age 18.5 yrs) and an age-matched control group were assessed for testicular hormones and DXA-derived bone mass. Results: Current median body mass indexes for the obese and control subjects were 37.4 kg/m2 and 22.9 kg/m2. Severe early-onset obesity manifested with lower free testosterone [median (inter-quartile range) 244 (194–332) vs. 403 (293–463) pmol/l, P=0.002]. Lower insulin-like 3 [1.02 (0.82–1.23) vs. 1.22 (1.01–1.46) ng/mL, P=0.045] and lower ratio of testosterone to LH [2.81 (1.96 – 3.98) vs. 4.10 (3.03 – 5.83) nM/IU, P=0.008] suggested disrupted Leydig cell function. Degree of current obesity correlated inversely with free testosterone (τ=-0.516, P=0.003), which in turn correlated positively with bone area at all measurement sites in males with childhood-onset obesity. Conclusions: Severe childhood-onset obesity associates with impaired Leydig cell function in young men and lower free testosterone may contribute to impaired bone growth.